Pengaruh Kelompok Kerja Guru (KKG) dan Profesionalisme Guru terhadap Prestasi Belajar Matematika Siswa SD Kecamatan Deket Kabupaten Lamongan - Wiwik Wahyu Widiastuti (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Teachers have a strategic role for creating vision of organizing learning based on the principle of professionalism. The requirement of teachers for professional can’t avoided, because of more development of the times and more the students and guardian students critically. One of effort for upgrading the professionalism of teachers through share activities and discuss between teachers in teacher organization. It is called teacher working group. The aim of this research are for determining effects from teacher working group and professionalism of teachers to mathematics learning achievement of students in cluster IV, district Deket, Lamongan with partial or simultaneously. The teacher working group and professionalism data took from questionnaire in all primary schools that include cluster IV in Lamongan, it consist of Srirande 1, Srirande 2, Pandan Pancur 2, Pandan Pancur 3, Plosoboden, and Rejotengah 2. Mathematics learning achievement data took from the average scores of mid and final test. Teacher working group is measured from indicator planning, performing, and evaluating. It measured by 4 competition based on Regulation of the Minister of National Education of the Republic of Indonesia number 16 year 2007 about Academic Qualification Standard and Teacher’s Competence. It consist of pedagogic, personality, and social. The methods of analyses used are frequency’s tables, pie-chart, bar-chart, boxplot, descriptive statistics and t-test. The result showed teacher working group and professionalism of teachers variables give effect to Mathematics learning achievement with partial or simultaneously.